High-strength and high-plasticity lead-tin bronze alloy and preparation method thereof

By preparing semi-solid slurry and controlling the preheating temperature of the mold, the problems of insufficient strength and plasticity of traditional lead-tin bronze alloys are solved, and the preparation of high-strength and high-plastic lead-tin bronze alloys are realized, meeting higher usage needs.

CN119876656AActive Publication Date: 2025-04-25KUNMING UNIV OF SCI & TECH

Patent Information

Application Number
CN202510083088.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-20
Publication Date
2025-04-25
Estimated Expiration
2045-01-20

AI Technical Summary

Technical Problem

Traditional lead-tin bronze alloys have shortcomings in strength and plasticity, especially CuSn10Pb2Ni3 alloy, which cannot meet the current high service conditions.

Method used

By preparing semi-solid slurry, the primary alpha phase is formed, the formation of dendrites is inhibited, the tissue is transformed into equiaxed crystals, and the alloy melt cooling rate is adjusted by controlling the mold preheating temperature, promoting the diffusion of solute elements, and combining with rapid oil-cooling treatment, the tissue is evenly distributed, and the content of the hard and brittle phases between the crystals is reduced.

Benefits of technology

It significantly improves the strength and plasticity of lead-tin bronze alloy, has better comprehensive mechanical properties, and can meet higher usage needs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119876656A_ABST
    Figure CN119876656A_ABST
Patent Text Reader

Abstract

The invention discloses a high-strength and high-plasticity lead-tin bronze alloy and a preparation method thereof, and belongs to the technical field of copper alloy preparation. The method comprises the following steps: (1) carrying out induction heating smelting on the lead-tin bronze alloy, carrying out deoxidization, degassing and deslagging treatment, and standing and homogenizing an alloy melt after the surface of the alloy melt is pushed aside to form a mirror surface shape; (2) performing chilling modification treatment on the alloy melt subjected to standing homogenization in the step (1) to obtain semi-solid slurry; and (3) the semi-solid slurry obtained in the step (2) is poured into a preheating mold to be subjected to extrusion forming, a casting obtained after extrusion forming is subjected to heat preservation in the mold for a certain time and then is rapidly subjected to oil cooling to the room temperature, and the lead-tin bronze casting is obtained. And (4) the lead-tin bronze casting is subjected to solid solution and aging treatment, and the high-strength and high-plasticity lead-tin bronze alloy is obtained. The prepared lead-tin bronze alloy has high strength and plasticity at the same time, and higher use requirements can be met.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of copper alloy preparation, and specifically relates to a high-strength and high-plasticity lead-tin bronze alloy and a preparation method thereof Background Art

[0002] Lead-tin bronze alloy has many advantages such as good anti-friction properties, high thermal conductivity, fatigue resistance and anti-seizure performance. It is often used to make wear-resistant parts such as bearings, bushings, pistons, and bushings. It is widely used in high-speed rail, shipbuilding, aviation and other fields.

[0003] Lead-tin bronze alloy adds lead to tin bronze, so that the granular lead phase is distributed on the matrix as soft particles, which plays a good lubricating role, thereby obtaining a lower friction coefficient and good wear resistance. However, the addition of lead elements will cause embrittlement of the alloy grain boundaries, seriously reducing the ductility of the alloy. The lead-tin bronze alloy prepared by the traditional lead-tin alloy component production process has relatively serious Pb element specific gravity segregation and Sn element reverse segregation, and is prone to defects such as looseness and cracks, resulting in a serious reduction in the strength and plasticity of the lead-tin bronze alloy, especially the CuSn10Pb2Ni3 alloy.

[0004] CuSn10Pb2Ni3 alloy is one of the important materials for hydraulic machinery of aircraft engines. It is usually used in combination with steel to form plunger pump rotors and sliding shoes. With the development of society, the strength and plasticity of the alloy produced by traditional technology cannot meet the current service conditions.

[0005] Therefore, it is necessary to provide a high-strength and high-plasticity lead-tin bronze alloy and a preparation method thereof to improve the strength and plasticity of the lead-tin bronze alloy, especially for the CuSn10Pb2Ni3 alloy, so that the performance of the lead-tin bronze alloy is better and meets the requirements of existing service conditions. Summary of the invention

[0006] In order to overcome the problems in the background technology, the present invention prepares a semi-solid slurry, forms a primary α phase in the slurry, inhibits the formation of dendrites in the subsequent solidification structure, and transforms the structure into equiaxed crystals. At the same time, by controlling the mold preheating temperature, the mold temperature is used to reduce the cooling rate of the alloy melt during the extrusion forming process, so that the solute elements enriched at the front of the solid / liquid interface during the solidification of the alloy melt can be fully diffused into the remaining liquid phase, and then combined with rapid oil cooling to inhibit the precipitation of Sn elements from the matrix, so that the structure after solidification is evenly distributed, and the content of intergranular hard and brittle phases is reduced, thereby improving the strength and plasticity of the lead-tin bronze alloy.

[0007] In order to achieve the above object, the present invention is implemented by the following technical solutions:

[0008] In one aspect, the present invention provides a method for preparing a high-strength and high-plasticity lead-tin bronze alloy, the preparation method comprising the following steps:

[0009] (1) Induction heating is performed on the lead-tin bronze alloy and the alloy is deoxidized, degassed and deslaged. After the surface of the alloy melt is mirror-like, the alloy melt is allowed to stand and be homogenized;

[0010] (2) subjecting the alloy melt after being allowed to stand and homogenize in step (1) to a quenching modification treatment to obtain a semi-solid slurry;

[0011] (3) pouring the semi-solid slurry obtained in step (2) into a preheated mold for extrusion molding, and then rapidly cooling the extruded casting to room temperature after keeping the casting in the mold for a certain period of time, thereby obtaining a lead-tin bronze casting;

[0012] (4) The lead-tin bronze casting is subjected to solid solution + aging treatment to obtain a high-strength and high-plasticity lead-tin bronze alloy.

[0013] Preferably, in step (1), the melting temperature of the lead-tin bronze alloy is 1200°C to 1250°C.

[0014] Preferably, in the step (1), 1% by mass of CuP14 is added to the alloy melt to carry out deoxidation, degassing and deslagging treatment.

[0015] Preferably, in step (1), the static homogenization temperature is 1065° C. to 1085° C., and the insulation time is 25 to 30 minutes.

[0016] Preferably, in step (2), the cooling rate of the quenching is ≥500°C / s.

[0017] Preferably, in step (3), the extrusion molding pressure ratio is 110 MPa to 150 MPa, and the extrusion rate is 20 mm / s to 24 mm / s.

[0018] Preferably, in step (3), the mold preheating temperature is 550°C to 600°C.

[0019] Preferably, in step (3), after extrusion molding, the casting is kept warm in a mold at 550°C to 600°C for 1 to 3 minutes, and oil-cooled to room temperature for 5-6 minutes.

[0020] Preferably, in step (4), the solution treatment temperature is 580°C to 650°C, the solution treatment time is 16 to 20 hours, and after the solution treatment, an aging treatment is performed at a temperature of 160 to 200°C, and the aging treatment time is 6 to 8 hours.

[0021] Another aspect of the present invention provides a lead-tin bronze alloy, which is prepared by the above-mentioned preparation method.

[0022] The reason for the poor performance of lead-tin bronze alloy is that: with the increase of tin content, especially when the tin content is greater than 8%, the solid solution strengthening effect of α solid solution formed by tin in the copper matrix is ​​enhanced, and the number of intergranular phases also increases. The hard and brittle tin-rich phase will lead to the improvement of alloy hardness, strength and wear resistance, while the ductility of the alloy is reduced and the brittleness is increased; at the same time, the lead-tin bronze alloy with a higher tin content will produce serious macroscopic segregation and microscopic dendrite segregation during gravity casting. In addition, the presence of lead elements with a larger specific gravity is also accompanied by lead specific gravity segregation. The presence of segregation will have a particularly adverse effect on the performance of the alloy. In addition, since the solidification process of lead-tin bronze alloy belongs to paste solidification, the alloy is very prone to casting defects such as hot cracks, pores, shrinkage, etc., resulting in poor comprehensive mechanical properties of the alloy. The present invention solves the above problems in two directions: first, a semi-solid slurry is prepared by rapid quenching modification, and a certain amount of primary α phase is formed in the slurry to inhibit the formation of dendrites in the subsequent solidification structure, so that the structure is transformed into equiaxed crystals; secondly, by controlling the preheating temperature of the mold, the high mold temperature is used to reduce the cooling rate of the alloy melt during the extrusion forming process, so that the solute elements enriched at the front of the solid / liquid interface during the solidification process can be fully diffused into the remaining liquid phase, and then combined with subsequent rapid oil cooling to inhibit the precipitation of Sn elements from the matrix, so that the structure after solidification is evenly distributed and the content of intergranular hard and brittle phases is reduced. Through the coordinated regulation of rapid quenching modification technology and mold preheating, an alloy with a small amount of evenly distributed intergranular hard and brittle phase microstructure is prepared. Finally, solid solution and aging treatment are used to further improve element segregation and organizational uniformity, and a high-strength and high-plasticity lead-tin bronze alloy is prepared.

[0023] Beneficial effects of the present invention:

[0024] 1. The lead-tin bronze alloy prepared by the present invention has excellent strength and plasticity, good comprehensive mechanical properties, and can meet higher usage requirements.

[0025] 2. The present invention is different from the existing technology of improving alloy properties by adding alloy elements. It is the first time to use a semi-solid rheological extrusion method in a lead-tin bronze alloy, combining the rapid quenching modification technology of the melt with the high mold temperature technology, and synergistically regulating the microstructure of the alloy to prepare a high-strength and high-plasticity lead-tin bronze alloy, laying a good foundation for the expansion of fields such as the preparation of lead-tin bronze / steel dissimilar bimetallic composite materials.

[0026] 3. The preparation process of the present invention is relatively simple, low-cost, high-efficiency, and can continuously prepare semi-solid slurry. It can be achieved using existing forming equipment such as extrusion and die-casting, and is suitable for industrial promotion and application. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 It is a schematic diagram of the process flow of the preparation method of the present invention;

[0028] Figure 2 This is a microstructure diagram of the high-strength and high-plasticity lead-tin bronze alloy prepared in Example 1 of the present invention;

[0029] Figure 3 This is a microstructure diagram of the high-strength and high-plasticity lead-tin bronze alloy prepared in Example 2 of the present invention;

[0030] Figure 4 This is a microstructure diagram of the high-strength and high-plasticity lead-tin bronze alloy prepared in Example 3 of the present invention;

[0031] Figure 5 This is a microstructure diagram of the high-strength and high-plasticity lead-tin bronze alloy prepared in Example 4 of the present invention;

[0032] Figure 6 The microstructure of the lead-tin bronze alloy prepared in the comparative example;

[0033] Figure 7 The stress-strain curves of the lead-tin bronze alloys prepared in Examples 1-4 and Comparative Examples of the present invention. DETAILED DESCRIPTION

[0034] The present invention is further described in detail below in conjunction with the accompanying drawings and specific embodiments, but the protection scope of the present invention is not limited to the described contents.

[0035] In the examples and comparative examples of the present invention, chemical reagents not otherwise specified were commercially available analytically pure reagents for the experiments.

[0036] In the embodiments of the present invention and the comparative examples, CuSn10Pb2Ni3 alloy is used as the initial raw material.

[0037] Example 1

[0038] This embodiment prepares a high-strength and high-plasticity lead-tin bronze alloy by the following method:

[0039] (1) Weigh 3 kg of CuSn10Pb2Ni3 alloy block and heat it in a medium frequency induction furnace at a melting temperature of 1250°C. At the same time, add 0.03 kg of CuP14 to the melt for deoxidation, degassing and deslagging until the surface of the melt is mirror-like. After the temperature of the alloy melt drops to 1085°C, let it stand and keep warm for 25 min for homogenization.

[0040] (2) The alloy melt after static homogenization is subjected to a quenching modification treatment by a rapid quenching device at a cooling rate of 500°C / s, and a semi-solid slurry is received in a crucible preheated to 1020°C.

[0041] (3) The semi-solid slurry is poured into a mold at a temperature of 550°C and directly extruded at a forming pressure of 110 MPa and an extrusion rate of 22 mm / s. After being kept warm in the mold for 2 minutes, the slurry is taken out and quickly oil-cooled for 5-6 minutes to obtain a lead-tin bronze casting.

[0042] (4) The lead-tin bronze casting was solution treated at 600°C for 20 h and then aged at 200°C for 6 h to obtain a high-strength and high-plasticity CuSn10Pb2Ni3 alloy.

[0043] The CuSn10Pb2Ni3 alloy prepared in this example was observed. Figure 2 The stress-strain curve of the alloy prepared in this embodiment is shown in Figure 7 shown.

[0044] pass Figure 2 It can be seen that in the lead-tin bronze alloy prepared in this embodiment, the grains are fine, the structure is transformed into equiaxed crystals, and the intergranular phase is significantly reduced, which is beneficial to improving the plasticity of the alloy.

[0045] Example 2

[0046] (1) Weigh 3 kg of CuSn10Pb2Ni3 alloy block and heat it in a medium frequency induction furnace at a melting temperature of 1240°C. At the same time, add 0.03 kg of CuP14 to the melt for deoxidation, degassing and deslagging until the surface of the melt is mirror-like. After the temperature of the alloy melt drops to 1075°C, let it stand and keep warm for 30 min for homogenization.

[0047] (2) The alloy melt after static homogenization is subjected to a quenching modification treatment by a rapid quenching device at a cooling rate of 550°C / s, and a semi-solid slurry is received in a crucible preheated to 1020°C.

[0048] (3) The semi-solid slurry is poured into a mold at a temperature of 570°C and directly extruded at a forming pressure of 130 MPa and an extrusion rate of 20 mm / s. After being kept warm in the mold for 3 minutes, the slurry is taken out and quickly oil-cooled for 5-6 minutes to obtain a lead-tin bronze casting.

[0049] (4) The lead-tin bronze casting was solution treated at 600°C for 16 h and then aged at 160°C for 8 h to obtain a high-strength and high-plasticity CuSn10Pb2Ni3 alloy.

[0050] The CuSn10Pb2Ni3 alloy prepared in this example was observed. Figure 3 The stress-strain curve of the alloy prepared in this embodiment is shown in Figure 7 shown.

[0051] pass Figure 3It can be seen that in the high-strength and high-plasticity CuSn10Pb2Ni3 alloy prepared in this embodiment, compared with Example 1, the intergranular hard and brittle phase content is further reduced, and the microstructure is evenly distributed, which is beneficial to further improve the strength and plasticity of the alloy.

[0052] Example 3

[0053] (1) Weigh 3 kg of CuSn10Pb2Ni3 alloy block and heat it in a medium frequency induction furnace at a melting temperature of 1250°C. At the same time, add 0.03 kg of CuP14 to the melt for deoxidation, degassing and deslagging until the surface of the melt is mirror-like. After the temperature of the alloy melt drops to 1065°C, let it stand and keep warm for 30 min for homogenization.

[0054] (2) The alloy melt after static homogenization is subjected to a quenching modification treatment by a rapid quenching device at a cooling rate of 600°C / s, and a semi-solid slurry is received in a crucible preheated to 1020°C.

[0055] (3) The semi-solid slurry is poured into a mold at a temperature of 580° C. and directly extruded at a forming pressure of 150 MPa and an extrusion rate of 22 mm / s. After being kept warm in the mold for 3 minutes, the slurry is taken out and quickly oil-cooled for 5-6 minutes to obtain a lead-tin bronze casting.

[0056] (4) The lead-tin bronze casting was solution treated at 580°C for 16 h and then aged at 180°C for 6 h to obtain a high-strength and high-ductility CuSn10Pb2Ni3 alloy.

[0057] The CuSn10Pb2Ni3 alloy prepared in this example was observed. Figure 4 The stress-strain curve of the alloy prepared in this embodiment is shown in Figure 7 shown.

[0058] pass Figure 4 It can be seen that in the high-strength and high-plasticity CuSn10Pb2Ni3 alloy prepared in this embodiment, the intergranular hard and brittle phases are relatively small and evenly distributed, and the grain size is also relatively small, which is conducive to improving the deformation synergy of the alloy and maximizing the strength and plasticity of the alloy.

[0059] from Figure 4 It can be found that when the mold preheating temperature is 580℃, the intergranular hard and brittle phases are less and evenly distributed, and the grain size is also relatively small, which is conducive to improving the deformation synergy of the alloy and maximizing the strength and plasticity of the alloy. At this time, the strength and plasticity are the best, such as Figure 7 shown.

[0060] Example 4

[0061] (1) Weigh 3 kg of CuSn10Pb2Ni3 alloy block and heat it in a medium frequency induction furnace at a melting temperature of 1200°C. At the same time, add 0.03 kg of CuP14 to the melt for deoxidation, degassing and deslagging until the surface of the melt is mirror-like. After the temperature of the alloy melt drops to 1065°C, let it stand and keep warm for 28 min for homogenization.

[0062] (2) The alloy melt after static homogenization is subjected to a quenching modification treatment by a rapid quenching device at a cooling rate of 600°C / s, and a semi-solid slurry is received in a crucible preheated to 1020°C.

[0063] (3) The semi-solid slurry is poured into a mold at a temperature of 600°C and directly extruded at a forming pressure of 150 MPa and an extrusion rate of 24 mm / s. After being kept warm in the mold for 1 minute, the slurry is taken out and quickly oil-cooled for 5-6 minutes to obtain a lead-tin bronze casting.

[0064] (4) The lead-tin bronze casting was solution treated at 650°C for 18 h and then aged at 180°C for 7 h to obtain a high-strength and high-plasticity CuSn10Pb2Ni3 alloy.

[0065] The CuSn10Pb2Ni3 alloy prepared in this example was observed. Figure 5 The stress-strain curve of the alloy prepared in this embodiment is shown in Figure 7 shown.

[0066] pass Figure 5 It can be seen that in the alloy prepared in this embodiment, the content of intergranular hard and brittle phases and the grain size have increased, and the alloy performance is slightly reduced compared with Example 3. Therefore, in the preparation method of the present invention, parameter regulation has an impact on the alloy performance. The parameter range in the preparation method of the present invention is relatively reasonable, which can play a good role in improving the alloy performance.

[0067] Comparative Example

[0068] This comparative example adopts the same method as Example 3 to treat the lead-tin bronze alloy, except that: in this comparative example, no chilling modification is performed, and the alloy melt after static homogenization is directly poured into the mold.

[0069] The CuSn10Pb2Ni3 alloy prepared in this example was observed. Figure 6 The stress-strain curve of the alloy prepared in this embodiment is shown in Figure 7 shown.

[0070] pass Figure 6It can be seen that in the alloy prepared in this embodiment, the microstructure is coarse, mainly dendritic structure, the hard and brittle phases are connected into sheets and the content is high. During tensile deformation, the hard and brittle phases are prone to cracks, which expand the extension trend of the cracks, split the matrix, and reduce the strength and plasticity of the alloy.

[0071] pass Figure 7 It can be seen that the alloy prepared in Example 3 of the present invention has the best strength and plasticity. At the same time, compared with the comparative alloy, the strength of the alloy in Example 3 is increased by 40.3%, and the plasticity is increased by 228%. Therefore, the preparation method of the present invention can significantly improve the strength and plasticity of the lead-tin bronze alloy.

[0072] In summary, the strength and plasticity of lead-tin bronze alloy can be significantly improved by rapid quenching modification of the melt, followed by appropriate high mold temperature and reasonable process parameters.

[0073] Finally, it should be noted that the above preferred embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail through the above preferred embodiments, those skilled in the art should understand that various changes can be made in form and details without departing from the scope defined by the claims of the present invention.

Claims

1. A method for preparing a high-strength and high-plasticity lead-tin bronze alloy, characterized in that: The preparation method comprises the following steps: (1) Induction heating is performed on the lead-tin bronze alloy and the alloy is deoxidized, degassed and deslaged. After the surface of the alloy melt is mirror-like, the alloy melt is allowed to stand and be homogenized; (2) subjecting the alloy melt after being allowed to stand and homogenize in step (1) to a quenching modification treatment to obtain a semi-solid slurry; (3) pouring the semi-solid slurry obtained in step (2) into a preheated mold for extrusion molding, and then rapidly cooling the extruded casting to room temperature after keeping the casting in the mold for a certain period of time, thereby obtaining a lead-tin bronze casting; (4) The lead-tin bronze casting is subjected to solid solution + aging treatment to obtain a high-strength and high-plasticity lead-tin bronze alloy.

2. The preparation method according to claim 1, characterized in that: In the step (1), the melting temperature of the lead-tin bronze alloy is 1200°C to 1250°C.

3. The preparation method according to claim 1, characterized in that: In the step (1), 1% of the mass of the alloy melt, CuP14, is added to the alloy melt for deoxidation, degassing and deslagging.

4. The preparation method according to claim 1, characterized in that: In the step (1), the static homogenization temperature is 1065° C. to 1085° C., and the insulation time is 25 to 30 minutes.

5. The preparation method according to claim 1, characterized in that: In the step (2), the cooling rate of the quenching is ≥500°C / s.

6. The preparation method according to claim 1, characterized in that: In the step (3), the extrusion molding pressure ratio is 110 MPa to 150 MPa, and the extrusion rate is 20 mm / s to 24 mm / s.

7. The preparation method according to claim 1, characterized in that: In the step (3), the mold preheating temperature is 550°C to 600°C.

8. The preparation method according to claim 1, characterized in that: In the step (3), after extrusion molding, the casting is kept in a mold at 550°C to 600°C for 1 to 3 minutes, and the time for oil cooling to room temperature is 5-6 minutes.

9. The preparation method according to claim 1, characterized in that: In the step (4), the solution treatment temperature is 580°C to 650°C, and the solution treatment time is 16 to 20 hours. After the solution treatment is completed, an aging treatment is performed, and the aging treatment temperature is 160 to 200°C, and the aging treatment time is 6 to 8 hours.

10. A high-strength and high-plasticity lead-tin bronze alloy, characterized in that: The high-strength and high-plasticity lead-tin bronze alloy is prepared by the preparation method described in any one of claims 1 to 9.

Citation Information

Patent Citations

  • Cast wear-resistant tin bronze alloy and preparation method thereof

    CN102304642A

  • High strength and high elasticity tin bronze alloy and solid solution process thereof

    CN107604203A

  • High-strength wear-resistant high-lead tin bronze material and preparation method thereof

    CN113462926A

  • Tin-lead bronze bar and preparation method thereof

    CN115261669A

  • High-strength and high-plasticity tin bronze alloy and preparation method thereof

    CN116254436A

Cited By

  • Preparation method of high-strength and high-toughness lead-tin bronze bar

    CN120138426A